Effect of Nitrogen Fertilization Dosage on Growth and Results Tobacco on Tobacco Plant Cigar (Nicotiana tabacum L.) - Afandi Bastian (Contributions of Central Research Institute for Agriculture, 2022)
This research was to study the effect of N fertilizer doses on the growth, yield and quality of Besuki Na Oogst tobacco plants. The hypothesis put forward is. (1). Application of N fertilizer at certain doses can increase the growth and yield of Besuki Na Oogst tobacco plants. (2). Application of N fertilizer at certain doses can improve the quality of Besuki Na Oogst tobacco plants. The results of the study generally revealed that there were significant differences in the treatment of nitrogen fertilizer doses in the parameters of length, width and area of krosok leaves, production leaf weight parameters and Dekblad and Omblad leaf weights per harvest. On leaf weight production and leaf quality of Dekblad and Omblad, treatment with a fertilizer dose of 50 kg N/ha gave the lowest yield and was significantly different from the other treatments. and treatment of fertilizer doses of 100 kg N/ha to 250 kg N/ha gave results that were not significantly different. Observations made during the study included growth which consisted of leaf length, leaf width, leaf area and number of leaves, harvest observations consisted of leaf gross weight, and post-harvest observations consisted of plant nitrogen analysis, nicotine analysis and quality analysis. The data obtained was tested by analysis of variance (F test) and continued with Duncan's test (p;0.05).